Toward A History of Canadian Wallpaper Use: Mechanization 1860-1935 - Kelly, Robert (Material Culture Review)

(untitled) (Cape Breton University Press, 2014)
Abstract This article examines wallpaper use in Canada from the beginning of cylinder printing in 1860 to 1935. Statistics reveal that the value of wallpaper within Canada grew steadily during this period, before declining precipitously during the 1930s. Canada’s four major factories achieved dominance in their home market by producing low-to-middle grade wallpaper at affordable prices. This paper documents this achievement and explores its significance, centering on a key compilation of primary and secondary sources. From this compilation, costs and patterns of trade are extracted in order to show Canadian development against the backdrop of wallpaper history. Partial comparison to Canada’s chief competitor and trading partner, the United States, is made through analysis of per capita production and consumption figures. This article is grounded in recent scholarship from Europe which suggests that wallpaper can be viewed as an object of use over and above its more familiar role as a minor art-historical artifact.